Determining management factors of overall equipment efficiency in selected Malaysian public universities - Ngadiman, Yunos (2017)
Overall Equipment Efficiency (OEE) is a fundamental method of measuring the equipment performance tool for bringing maintenance and engineering to address the higher level of organizational performance. Determining management factors of OEE in this study is to enhance the machining performance in the engineering laboratories at the selected Malaysian public university. Nowadays, the management of the capital equipment is regarded as moderately viewed and based on the existing rules of asset management. However, an understanding of the overall management of laboratory management still does not have the importance factor including the administrative management system of laboratory equipment such as the training program of technical staff, capital equipment management, equipment maintenance and reliability engineering management without seeing the further machining performance. The engineering expert opinions was accounted and consistently agreed that the determination of the capital equipment performance should be established to define the significance of evaluating the performance of equipment in Malaysian higher learning institutions. Acting in accordance from the expert, a study of determining the direction of the equipment performance benchmarking is needed. Therefore, beginning the stage of this research is conducted for the purpose of determined the relationship between the Capital Equipment Management Factor (CEMF) and OEE in university perspective. The research methods used throughout this research were quantitative methods with two methods applied. The first method is the calculating the OEE performance ratios of twenty-five selected lathe machine in the engineering laboratory of the Malaysian public universities. The second method conducts a survey questionnaire with face-to-face to answer the all questions provided. The respondents are comprised of experienced technical staff with more than five years working in the management of laboratory equipment. There are six factors of CEMF were identified which included General Organizational Management, Departmental Organizational Management, Technical Training Program, Capital Equipment Management, Maintenance Management, and Reliability Engineering Management. Survey data was analyzed through the statistical method of analysis using SPSS version 23.0 to determine the normality of data, the reliability of the question asked, Spearman correlation and hypothesis testing. The methodological tool of Spearman correlation was used to analyze the correlation relationship between the CEMF and Individual Perceiveness and OEE performance. Therefore, the findings of this study presented the correlation test for each factor of CEMF was correlated with Individual Perceiveness. Meanwhile, the null hypothesis tested was denied and the alternate hypothesis tested shown the positive and acceptable result. It showed the relationship between the CEMF with Individual Perceiveness and OEE was inter-correlated.